THE EFFORTS OF THE SAMAPTA PATROL UNIT IN PREVENTING THE CRIME OF THEFT WITH BALLAST AT THE KENDAL POLICE STATION - Mahatir Muhammad Hidayat (Police Studies Review, 2022)
The writing of this final task is motivated by a large number of theft crimes with ballast at Kendal police over the past three years. By prioritizing preventive methods, through the Turjawali unit, the samapta unit makes efforts to prevent theft with ballast at Kendal police by conducting patrol activities to prevent the emergence of intentions and opportunities in committing crimes. The purpose of this paper is to describe and analyze the implementation of the Samapta Unit Patrol Unit in preventing theft with a ballast at kendal police and also describe and analyze the form of the samapta unit patrol unit's efforts in preventing theft with a ballast at Kendal Police Station. As an analysis knife, the author uses several concepts and theories, namely: the concept of effort, the concept of Satsamapta, the concept of Patrol, the concept of theft with ballast, management theory, and crime prevention theory. With the research area in Kendal Police. This research is carried out with a qualitative approach, using field research types, as well as data collection techniques with observation, interviews, and document studies. In the results of this study, the authors found that in the implementation of Satsamapta patrols there are obstacles in the competence of inadequate personnel, disproportionate schedule arrangements due to lack of personnel, and the absence of making Kamtibmas messages and in its implementation has not been in accordance with the applicable provisions. Furthermore, the efforts made by the Samapta Unit Patrol Unit as a crime prevention effort have not been maximized. The conclusion of this study, is that the efforts made by Satsamapta through patrols are considered not optimal and there are several obstacles. The author provides input in the implementation of satsamapta Kendal Police Resort and conducted internal training by the Police Resort in order to improve the knowledge and abilities of members and implement the IDTRACK Server GPS application during patrol. Then the efforts made can be maximized by conducting socialization of Perkabaharkam number 1 of 2017 concerning patrols to the Kendal Police Satsamapta and coordinating with patrol units of the Sector Police in all jurisdictions of the Kendal Police.